Media, Teologi, dan Persepsi Jemaat Kristen Tentang Konflik Israel–Palestina: Tinjauan Literatur Sistematis - Markus Adifirmanu (Fakultas Ilmu Keguruan dan Pendidikan, Universitas Kristen Indonesia, 2026)
This study aims to analyze the influence of media and theological doctrine on Christian congregational perceptions of the Israel–Palestine conflict using a Systematic Literature Review (SLR) approach. The primary issue addressed is the polarization of congregational perceptions driven by biased media narratives, rigid theological interpretations, and their impact on human existence in conflict-affected regions. Employing the PRISMA protocol and Kitchenham standards, this study synthesizes final literature drawn from various academic databases published between 2020 and 2025. The findings indicate that congregational perceptions are constructed through a dialectical interaction between international media framing, doctrines of biblical land sovereignty, and the spiritual experiences of pilgrims. The study highlights the urgent need for church revitalization through media literacy and inclusive theology to promote social justice for marginalized communities. Ultimately, this research contributes to the development of a transformative Christian public ethics in responding to global humanitarian crises.